3-dimensional free-form object surface representation and its recognition using range images - Sun, Zehang. (2008)
This thesis presents a new approach-GICCA (Gaussian Image Combining Cur-vature and Characteristics-Array) to the representation and recognition of 3-D free-form rigid objects using range images. The approach can handle situations when (a) the objects may have arbitrary shapes or forms, (b) objects may be viewed from any directions, (c) objects may be partially occluded by other ob-jects, and (d) scenes may include multiple objects. This approach includes three parts: